The investigation of influence of laser radiation on the structure and mechanical properties of composite electrolytic nickel coating - Zabludovsky, V. A.; Dudkina, V. V.; Shtapenko, E. Ph. (Science and Transport Progress, 2013)
Purpose. Investigation of laser radiation effect on the structure and mechanical properties of electrodeposited nickel composite coatings containing ultrafine diamonds. Methodology. Electrodeposition of nickel films was carried out with the addition of a standard solution of ultrafine diamonds (UFD) on laser-electrolytic installation, built on the basis of the gas-discharge CO2 laser. Mechanical testing the durability of coatings were performed on a machine with reciprocating samples in conditions of dry friction against steel. The spectral microanalysis of the elemental composition of the film - substrate was performed on REMMA-102-02. Findings. Research of nickel coatings and modified ultrafine diamond electrodeposited under external stimulation laser demonstrated the dependence of the structure and mechanical properties of composite electrolytic coating (CEC), and the qualitative and quantitative distribution of nanodiamond coprecipitated from an electrodeposition method. Originality. The effect of laser light on the process of co-precipitation of the UFD, which increases the micro-hardness and wear resistance of electrolytic nickel coatings was determined. Practical value. The test method of laser-stimulated composite electrolytic nickel electrodeposition coating is an effective method of local increase in wear resistance of metal coatings, which provides durability save performance (functional) properties of the surface.